2010
DOI: 10.1016/j.jneuroim.2009.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Substance P downregulates expression of the high affinity IgE receptor (FcεRI) by human mast cells

Abstract: The effect of the neuropeptide substance P (SP) on human mast cell (MC) phenotype is poorly understood. In this study, SP effects on human MC expression of the high affinity IgE receptor (FcεRI) were characterized. SP downregulated expression of FcεRI mRNA and protein by approximately 50% and in a concentration dependent manner, the effect was partially mediated by engagement of the neurokinin-1 receptor (NK1R) and resulted in reduced mast cell activation. Sensitization of MC with IgE prior to SP exposure prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
(33 reference statements)
2
20
1
1
Order By: Relevance
“…Neurons and activated structural cells are capable of influencing the immune response through the release of cytokines and soluble mediators. One hypothesis could be a link with the production of substance P. This molecule plays a role in smooth muscle contraction, is elevated in the BALF of asthmatics (29,30), and downregulates the IgE receptor expression on mast cells (31). Furthermore, the induction of substance P in allergic asthma is dependant on another neurotrophin, NGF (32).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons and activated structural cells are capable of influencing the immune response through the release of cytokines and soluble mediators. One hypothesis could be a link with the production of substance P. This molecule plays a role in smooth muscle contraction, is elevated in the BALF of asthmatics (29,30), and downregulates the IgE receptor expression on mast cells (31). Furthermore, the induction of substance P in allergic asthma is dependant on another neurotrophin, NGF (32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SP can enhance the innate immune response to bacterial infections by upregulating TLR2 expression on mast cells (LAD2) . On the other hand, SP can also downregulate FcεRI expression on human mast cells (LAD2 and hPDMC), implying its role in the modulation of IgE-mediated allergic diseases (McCary et al, 2010). It has been established that SP activation of murine mast cells is NK1R mediated (Kulka et al, 2008;van der Kleij et al, 2003).…”
Section: Substance Pmentioning
confidence: 99%
“…Previous studies have indicated that intramural injection of substance P or selective neurokinin-1 receptor (SPR) agonist act on nervous system by interact with neurotransmitters. For example, electrophysiological studies revealed that substance P excited nigral dopaminergic neurons [18].Substance P has also been revealed to promote dopamine release from striatal dopamine terminals [19]- [20], which may be involved in maintaining the integrity of neuronal populations [21].…”
Section: A Sp Spr and Nervous Systemmentioning
confidence: 99%